2017
DOI: 10.1073/pnas.1614787114
|View full text |Cite
|
Sign up to set email alerts
|

Selection maintains signaling function of a highly diverged intrinsically disordered region

Abstract: Intrinsically disordered regions (IDRs) are characterized by their lack of stable secondary or tertiary structure and comprise a large part of the eukaryotic proteome. Although these regions play a variety of signaling and regulatory roles, they appear to be rapidly evolving at the primary sequence level. To understand the functional implications of this rapid evolution, we focused on a highly diverged IDR in Saccharomyces cerevisiae that is involved in regulating multiple conserved MAPK pathways. We hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 94 publications
8
87
0
Order By: Relevance
“…6d). These findings support the hypothesis that such homologous IDRs retain similar functions, despite extensive sequence divergence 45 .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…6d). These findings support the hypothesis that such homologous IDRs retain similar functions, despite extensive sequence divergence 45 .…”
Section: Resultssupporting
confidence: 83%
“…6b and 4h). As IDRs are generally evolving rapidly, at the primary sequence level, it is currently difficult to predict whether their functional consequences are preserved during the evolution of CYC/TB1-like proteins 45 .…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, we speculate that IDPs have a high tolerance to mutations (both neutral and adaptive) but also a selective propensity to preserve their structural disorder, i.e., flexibility and conformational dynamics under physiological conditions. In support of that, different experimental and computational analyses showed that function and dynamic behavior of intrinsically disordered proteins are under selection and they are conserved in the face of negligible sequence conservation (Daughdrill et al, 2007;Lemas et al, 2016;Zarin et al, 2017;Walter et al, 2019). Additionally, there could be a strong selection to reduce the adverse effects of large concentrations of IDPs by tightly controlling their expression at all levels of transcription, translation, and protein degradation (Gsponer et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Given the importance of specific amino-acid motifs, sequence composition, and sequence patterning [13][14][15][16], it is not obvious that statistical laws derived for homopolymers in the limit of infinitely long chains will always satisfactorily describe finite-length heteropolymeric IDPs. This conformational diversity will likely not be captured by a single mean-field descriptor of polymer behaviour, such as a scaling exponent Îœ, or a single global dimension, such as the radius of gyration R g .…”
Section: Introductionmentioning
confidence: 99%